Pembabitan Kearifan Tempatan Dalam Program Tanggungjawab Sosial Korporat: Kajian Kes Di Aqua Danone Mambal Plant Bali, Indonesia - Rosilawati, Yeni (2017)
This research aims to identify the local wisdom that is affecting the implementation of CSR by choosing a case study in Aqua Danone Mambal Plant in Bali, Indonesia. The first objective of this research is to identify the understanding of local wisdom from the perspective of Aqua Danone Mambal Plant and stakeholders. This includes local communities, community leaders and non-governmental organizations (NGOs). Secondly, this study seeks to analyze the planning process of Corporate Social Responsibility (CSR) Aqua Danone Mambal Plant. Thirdly, this research investigates and understands the implementation of CSR Programs. Fourthly, it will enhance the understanding about the monitoring process of Corporate Social Responsibility (CSR). Last but not least, this study seeks to identify the factors that lead to the adoption and restriction of the Corporate Social Responsibility (CSR).